Analysis of Patient Selection Patterns Among Female and Male Resident Physicians - Elise Bouchal; Kimberly Heller; Christopher Dodoo; Stephanie Hernandez; Isabella Reitz; Maile Wells; Marcella Torres; Douglas Rappaport (Emergency Care and Medicine, 2026)
Background: Gender disparities have been reported in Emergency Medicine (EM) residency milestone attainment, with some studies showing male residents achieving higher competency-based ratings than female residents despite similar clinical exposure. Prior research suggests subjective faculty evaluation and implicit bias may contribute to these differences. The influence of resident self-assignment of patients on milestone attainment remains unclear, and the potential contribution of differential patient exposure through self-selection has not been directly investigated. Objectives: To determine whether gender differences exist in the types of patients or acuity levels that EM residents self-assign to determine if this could potentially explain the differences seen in EM milestone achievement across genders. Methods: Design and Setting: Retrospective chart review of EM resident patient selection at the Mayo Clinic Arizona Emergency Department from September 2018 through December 2022. Patients: The study was conducted at a single academic emergency department with resident and attending physician staffing. The study was determined to be IRB exempt. Data Collection: Epic electronic medical record data included resident and attending gender, patient demographics, chief complaint, Emergency Severity Index (ESI) triage level, vital signs, method of arrival, and procedures performed. Statistical Analysis: Continuous variables were compared using Student’s t-test or Wilcoxon rank-sum test; categorical variables were compared using chi-square test. Significance was set at p < 0.05. Analyses were performed using SAS version 9.4. Results: A total of 14,279 cases were analyzed. No significant differences were observed between female and male residents in patient chief complaint, age, race, gender, means of arrival, attending gender (p = 0.10872), or total procedures performed (p = 0.23102). Female residents saw patients with higher initial respiratory rates (p = 0.04313) and trended non-significantly toward higher-acuity ESI levels 1–2 (p = 0.07214). Conclusion: When residents self-assign patients in the emergency department, no meaningful gender differences exist in patient selection, procedural exposure, or gender attending assignment. These findings suggest that observed gender disparities in milestone attainment are unlikely driven by clinical exposure or patient selection, supporting that other factors may contribute to these differences.